Melittin derived peptide-drug conjugate, M-DM1, inhibits tumor progression and induces effector cell infiltration in melanoma by targeting M2 tumor-associated macrophages - Jeong, Chanmi; Kim, Jeongdong; Han, Ik-Hwan; Kim, Soyoung; Choi, Ilseob; Kim, Hongsung; Jeong, Jin-Hyun; Bae, Hyunsu (Frontiers in Immunology, 2023)
Background Melanoma has the highest mortality rate among all the types of skin cancer. In melanoma, M2-like tumor-associated macrophages (TAMs) are associated with the invasiveness of tumor cells and a poor prognosis. Hence, the depletion or reduction of M2-TAMs is a therapeutic strategy for the inhibition of tumor progression. The aim of this study was to evaluate the therapeutic effects of M-DM1, which is a conjugation of melittin (M), as a carrier for M2-like TAMs, and mertansine (DM1), as a payload to induce apoptosis of TAMs, in a mouse model of melanoma. Methods Melittin and DM1 were conjugated and examined for the characterization of M-DM1 by high-performance liquid chromatography and electrospray ionization mass spectrometry. Synthesized M-DM1 were examined for in vitro cytotoxic effects. For the in vivo study, we engrafted murine B16-F10 into right flank of C57BL/6 female mice and administered an array of treatments (PBS, M, DM1, or M-DM1 (20 nmol/kg)). Subsequently, the tumor growth and survival rates were analyzed, as well as examining the phenotypes of tumor-infiltrating leukocytes and expression profiles. Results M-DM1 was found to specifically reduce M2-like TAMs in melanoma, which potentially leads to the suppression of tumor growth, migration, and invasion. In addition, we also found that M-DM1 improved the survival rates in a mouse model of melanoma compared to M or DM1 treatment alone. Flow cytometric analysis revealed that M-DM1 enhanced the infiltration of CD8+ cytotoxic T cells and natural killer cells (NK cells) in the tumor microenvironment. Conclusion Taken together, our findings highlight that M-DM1 is a prospective agent with enhanced anti-tumor effects.